Influence of Strategic Plan Implementation on Performance of Regulatory Institutions in Nairobi City County - Waweru, Patrick; Mangana, Robert (European Journal of Business and Strategic Management, 2024)
Purpose: The aim of the study was to examine the influence of strategic plans implementation on performance of regulatory institutions in Nairobi City County. Methodology: The scope of this study encompasses 81 regulatory institutions operating within Nairobi City County. The study used a cross-sectional survey design using a self-administered questionnaires. The target population for study is 33,886 employees of the 81 regulatory institutions in Nairobi City County. On the other hand, a sample size will be 246 respondents that will be arrived at through stratified random sampling. The quantitative information was collected by using standardized questionnaires given to sampled top management, middle level management and operational level staff in these regulatory institutions. Conversely, document analysis was used to acquire the qualitative data. The questionnaires were processed quantitatively while documentary evidences such as reports were analysed thematically. The data was presented in frequency tables. Findings: The study established that regulatory institutions were moderately engaging stakeholders in implementation of strategic plans. Notably, it was established that there existed challenges that hindered stakeholders’ collaboration. The study established that the allocated budget were averagely aligned to the strategic plans goals and initiatives. This meant that all the set objectives under strategic plans by these institutions could not be supported by the allocated budgets. The study also established that the management in these institutions were only communicating strategic vision and goals to employees at a moderate extent. In addition, there were deficiencies of skills capacity in certain areas in the implementation of strategic plans. The study determined these mechanisms were not well entrenched in these institutions. Unique Contribution to Theory, Practice and Policy: The study was anchored on performance contract theory. The study recommends that regulatory institutions should set clear strategic goals and objectives. Significantly, these institutions need to have clear communication strategies for their strategic goals, objectives and shared vision. Besides, they should improve their monitoring and evaluation mechanisms by having Key Performance Indicators (KPIs) in every strategic goal and objective that are specific, measurable, attainable, realistic and time bound. In addition, regulatory institutions should prioritize engagement of stakeholders throughout the implementation process. Finally, the study recommends allocation of adequate resources to regulatory institutions based on the programs set out in their strategic plans for effective implementation.